Young people with migration experience and their (non) encounters with Swedish sexual and reproductive health services and information: An explorative study - Nada Amroussia; Malin Lindroth; Catrine Andersson (Elsevier, 2024)
Although a growing body of literature has focused on the experience of young people with migration experience with Swedish sexual and reproductive health (SRH) services, there is a lack of deep qualitative exploration. The study aims to explore the encounters of young people with migration experience with SRH services and their understandings of factors that affect their use of these services. The findings of this study were drawn from 18 interviews conducted between October 2021 and May 2023 in Southern Sweden. A combination of convenient and snowball sampling strategies was used. Participants included in the study self-identified as Middle Eastern, migrated to Sweden, and were aged between 17 and 26. Data were analyzed using reflexive thematic analysis approach.Three themes were generated during the analysis. The first SRH services: dual perceptions and experiences shows how participants had ambivalent perceptions of SRH services, mainly the youth clinic. Some perceived the youth clinic as a stigmatized place associated with shame and SRH concerns like unwanted pregnancy and sexually transmitted infections, while others viewed the youth clinic as a safe space. The negative perceptions along with the difficulties with accessing the youth clinic contributed to low service use. The second Sexuality education: an eye-opener or a joke? reflects participants' both positive and negative experiences and attitudes when receiving sexuality education in schools. The third SRH information: beyond formal services and education captures participants' ways of accessing SRH information that go beyond information provided at the traditional SRH services and sexuality education in schools. These sources include the family, friends, and the internet. The study points to the need for multicomponent strategies to improve the accessibility of SRH services and draws attention to the importance of challenging norms related to Swedishness in sexuality education to foster the engagement of youth with migration experience and ensure their sexual citizenship.